(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
in recent years a spike is seen in mortality linked to heart disease. In developed countries mortality linked to heart diseases have seen a gradual decrease due to the availability of better medical facilities and public awareness but on the other hand in developing countries like India and other south Asian countries alarming increment of mortality linked to heart disease has been seen in recent years. According to a research published in Indian heart journal India has seen a 4 fold increment in mortality linked to heart disease in past 40 years [1]. Abundant amount of data is collected by various medical institutions in past a decade. The data is available on various open source platforms like UCI, KAGGLE, and other Government websites.in this paper we will review all the techniques of data mining, machine learning and deep learning used by the researches previously on these open source datasets. So that we can propose a better technique for early prediction of heart disease using machine learning and deep learning models.